Analysis of micro-shear bond strength of self-etch adhesive systems with dentine: An in vitro study - Vijay Kumar Shakya; Rajeev Kumar Singh; Anjani Kumar Pathak; Balendra Pratap Singh; Anil Chandra; Ramesh Bharti; Rakesh Kumar Yadav (Journal of Oral Biology and Craniofacial Research)
Background: Success or failure of a composite restoration largely depends on its bonding to enamel/dentine. Several better adhesive systems have been developed during the last few years due to rapid advancement in the technology. Recent self-etched adhesives have fewer clinical steps and are less technique sensitive. Methods: Ninety extracted human permanent molars were collected, grounded and finished to prepare flat dentine-bonding surfaces on their occlusal surface. All specimens were divided into three groups (n = 30) on the basis of three adhesive systems Adper Easy Bond (AE), Beautibond (BB) and Xeno IV (XE). These adhesive systems were applied on prepared mid-dentine-bonding surface. A restorative resin was added with the help of a transparent tube of 2 mm height and 1.7 mm internal diameter and cured. Fifteen specimens in each group were loaded to failure in an Instron Universal Testing Machine after storage for 24 h at 37 °C to check micro-shear bond strength. Another fifteen specimens from each group were thermocycled 500 times at 5 °C and 55 °C with dwell time of 1 min in each bath followed by loading to failure. The data obtained was analyzed with SPSS version 21 at significance level of <05. Results: After 24 h, micro-shear bond strength of BB was higher (26.04 MPa) than XE (23.69 MPa) and AE (21.50 MPa). After thermocycling, micro-shear bond strength decreased significantly in BB (P = .001) and XE (P = .03). Conclusion: The micro-shear bond strength of BB was highest among three groups, which decreased after thermocycling.